Assembly patterns of mixed‐species avian flocks in the Andes. (20th October 2014) - Colorado, Gabriel J.; Rodewald, Amanda D.; Meiri, Shai
Summary The relative contribution of deterministic and stochastic processes in the assembly of biotic communities is a central issue of controversy in community ecology. However, several studies have shown patterns of species segregation that are consistent with the hypothesis that deterministic factors such as competition and niche‐partitioning structure species assemblages in animal communities. Community assembly provides a theoretical framework for understanding these processes, but it has been seldom applied to social aggregations within communities. In this research, we assessed patterns of non‐randomness in Andean mixed‐species flocks using three assembly models: (i) co‐occurrence patterns; (ii) guild proportionality; and (iii) constant body‐size ratios using data from 221 species of resident and Neotropical migrant birds participating in 311 mixed‐species flocks at 13 regions distributed in Venezuela, Colombia, Ecuador and Peru. Significant assembly patterns for mixed‐species flocks based on co‐occurrence models and guild proportionality models suggest that competitive interactions play an important role in structuring this social system in the Andes. Distribution of species among foraging guilds (i.e. insectivore, frugivore, omnivore, nectivore) was generally similar among flocks, though with some regional variation. In contrast, we found little evidence that structuring of mixed‐species flocks in the Andes was mediated by body size. Rather, we found greater than expected variance of body‐size ratios within flocks, indicating that birds did not segregate morphologically. Overall, our findings suggest that deterministic factors associated to competitive interactions are important contributors to mixed‐species flock assemblages across the Andes.